Study of nursing method for hemodialysis patients after due consideration of their whole personalities - Ikeda, Yasunobu; Makino, Hihumi; Hattori, Mutsuko; Inoue, Reiko; Nishigaki, Keiko; Nakahara, Fumio; Nomura, Naomi; Ohno, Yasuyo; Uesugi, Nanori (Journal of Japanese Society for Dialysis Therapy, 1991)
Nursing care to aid social and mental problems, after due consideration of the patients' whole personalities, is necessary in patients with chronic hemodialysis. In this study, we arranged and analyzed systematically various information about patients. The subjects were ten patients undergoing chronic maintenance hemodialysis for about five years (from one month to fourteen years). Six patients were male and four were female. The average age was 55.9±9.8 years. The underlying diseases were chronic glomerulonephritis (n=9) and diabetes mellitus (n=1). As analysis methods for information, we used the “Fish-bone” type analysis, “Sequence of events” (Hurst), egogram (TEG), and the “Cobweb” type of analysis. We discussed these methods in case conferences and performed mental nursing care according to the “Cobweb” type analysis. As the nursing evaluation method, we applied “grief level” assessment of patients by Duke University Hospital. Therefore, we were better able to understand the mental states of patients and performed nursing care easily. After that, shock and depression of the grief level in patients decreased significantly, and patients were able to progress smoothly to the next step of acceptance and settle their problems or anxieties. United action in nursing care could be performed by repitition of conferences, and nurses could take care of patients with gentleness and understanding. Consequently, it seems that patients could better understand their physical and mental states and accept their new hemodialysis lives.